The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1108/jcp-01-2021-0003
|View full text |Cite
|
Sign up to set email alerts
|

High resting heart rate protects against childhood risk factors in predicting adult psychopathy

Abstract: Purpose Previous research has indicated that low resting heart rate (RHR), measured at age 18, predicts later psychopathy, and that high RHR acts as a protective factor in nullifying the influence of several psychosocial risk factors in predicting later antisocial and criminal outcomes. This paper aims to investigate high RHR as a protective factor against age 8–10 psychosocial risk factors in predicting psychopathy factors at age 48 (measured by the PCL:SV). Design/methodology/approach Data collected in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…It is, of course, desirable that this type of cross-national comparative research should be replicated, preferably with large representative samples and using the same measuring instruments. It is also important to study risk factors for antisocial behaviour (Farrington and Aguilar-Carceles, 2023; Jackson, 2017; Juni, 2014; McGauran et al , 2019), including very early risk factors (Zara et al , 2023) and biological risk factors (Bergstrom and Farrington, 2018; Farrington and Bergstrom, 2021). Information about differences in risk factors might help to explain differences in prevalence and frequency between Chinese and American children.…”
Section: Discussionmentioning
confidence: 99%
“…It is, of course, desirable that this type of cross-national comparative research should be replicated, preferably with large representative samples and using the same measuring instruments. It is also important to study risk factors for antisocial behaviour (Farrington and Aguilar-Carceles, 2023; Jackson, 2017; Juni, 2014; McGauran et al , 2019), including very early risk factors (Zara et al , 2023) and biological risk factors (Bergstrom and Farrington, 2018; Farrington and Bergstrom, 2021). Information about differences in risk factors might help to explain differences in prevalence and frequency between Chinese and American children.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, they decided to dichotomise them into high (10 or more) versus low (0-9) PCL:SV scores and found that high scorers were qualitatively different from low scorers. They also dichotomised into high F1-PP (3þ) and high F2-PB (5þ) scores; dichotomised variables permit an easy and very understandable method of studying how predictors influence outcomes (Farrington and Bergstrøm, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…This is an important gap to address, as the study of these factors may have implications for how we understand the development of psychopathy, bridging our knowledge between biological, psychological and social factors. Farrington and Bergstrøm (2021) investigated the extent to which early risk factors, measured at ages 8-10, could predict psychopathy in adulthood, at age 48. They investigated the risk factors which were judged to be most important in the Cambridge Study in Delinquent Development (CSDD).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This approach is in line with Farrington and Loeber (2000). Another justification for the dichotomization of psychopathy scores follows from the fact that they are nonlinearly related to offending and to violence (see, e.g., Farrington & Bergstrom, 2018, 2021a), suggesting that the minority of high scorers are qualitatively different from the majority of low scorers. To assess the stability of psychopathy, odds ratios (OR) were calculated between each pair of successive time points.…”
Section: Analysesmentioning
confidence: 99%